2013
DOI: 10.1089/jwh.2012.3988
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Colon Cancer Treatment

Abstract: In Alabama, some gender differences in stage-specific colon cancer treatment are worth further scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
6
1
Order By: Relevance
“…In some other age groups, we could even detect an opposite trend. The overall lower rate of administration of adjuvant chemotherapy has been described for other regions; however, it has not yet been described in Germany [18]. Whether this is mainly caused by the older age of women at the time of diagnosis which has previously been discussed, our results support these findings, as the lower rate of adjuvant chemotherapy was particularly apparent in the age group over 80 years.…”
Section: Discussionsupporting
confidence: 85%
“…In some other age groups, we could even detect an opposite trend. The overall lower rate of administration of adjuvant chemotherapy has been described for other regions; however, it has not yet been described in Germany [18]. Whether this is mainly caused by the older age of women at the time of diagnosis which has previously been discussed, our results support these findings, as the lower rate of adjuvant chemotherapy was particularly apparent in the age group over 80 years.…”
Section: Discussionsupporting
confidence: 85%
“… also reported that the rate of ACT was lower among older Stage III patients. Although the rate of ACT has been reported to be higher in men than in women , the rate in our study was higher in women, possibly due to sociodemographic factors. The rate of administration of ACT in our study was lower in patients with N1 tumours than in those with N2 tumours, indicating that physicians might have employed an observation strategy in cases of CRC with a small number of LN metastases; we also found low rates of ACT in patients with lymphatic invasion, as has been reported previously .…”
Section: Discussioncontrasting
confidence: 88%
“…The cumulative risk of developing colon cancer before 75 years is 1.51% and 1.12% for men and women, respectively, giving a rate of 1 in 66 men and 1 in 89 women to develop CC [ 2 ]. Despite recent advances in chemotherapy and radiotherapy for CC, surgical resection remains the primary treatment, but there are gender differences in CC treatment choices [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%